Coupling coordination analysis of the economic-social-infrastructure-ecological resilience system: A case study of Zhejiang Province - Menglin Zhang; Yuchen Hu; Yihua Mao; Jiaqi Yang (PLoS ONE, 2025)
Nowadays, with the acceleration of urbanization and the profound impact of climate change, urban resilience has become a key issue for sustainable development. Through the panel data of Zhejiang Province from 2014 to 2022, this study employs the coupling coordination degree (CCD) model to analyze the coupling coordination relationship of the Economic-Social-Infrastructure-Ecological resilience (ESIE) quaternary system and binary systems. The impact of the CCD of each binary system on the overall CCD is determined by the grey correlation model considering alongside the current state of the coupling coordination development to identify the key binary system that promotes the development of the overall coordination. It finds that the CCD of the ESIE quaternary system in Zhejiang’s cities exhibits a consistent upward trend, and spatially, a pattern of coordinated regional urban development centered on the city of Hangzhou and Ningbo emerges. The CCD analysis of binary systems reveals a low level of pairwise CCD between economic, infrastructure and social resilience, with prominent contradictions between the three. Additionally, the CCD of the economic-infrastructure resilience binary system is the core issue currently faced by the overall coordinated development of the ESIE quaternary system. This research not only provides a new perspective for understanding the intrinsic mechanism of coupled and coordinated development of urban resilience but also offers a scientific basis for crafting sustainable urban policies.